Surgical outcomes of Endoscopic Anterior Cricoid Split and Balloon dilation as treatment for paediatric subglottic stenosis: a retrospective case series - Brownell, Louisa (Division of General Surgery, 2025)
Objective: Subglottic stenosis (SGS), congenital or acquired, can present as life-threatening airway emergencies or ongoing respiratory symptoms in paediatric patients. In resource-limited settings, identifying a first-line surgical option to definitively manage SGS, as opposed to permanent tracheostomy, is the ideal. The aim of this study is to review endoscopic anterior cricoid split with balloon dilation (EACSBD) as the first-line definitive treatment option for selective SGS cases, in a resource-limited setting, and to retrospectively compare outcomes with published literature. Study design: Retrospective Case Series Setting: Tertiary Paediatric State Hospital in Cape Town, South Africa. Methods: Medical records of children with SGS managed with EACSBD from Jan 2020 to July 2021 were reviewed. Data collected included preoperative characteristics, intraoperative findings, postoperative course, and clinical outcomes. Successful treatment was defined as resolution of symptoms with no baseline respiratory distress. Institutional ethical approval was obtained prior to commencement. Results: Eight patients aged between 3-17 months (mean age of 6,8 months) were identified. Cotton-Myer grades ranged between 1-3. The aetiology of the subglottic stenoses were: 4 acquired, 3 congenital, 1 mixed. Five patients did well with no further intervention necessary. One patient required a single follow-up laryngoscopy and balloon dilation. Overall, 6 patients (75%) had successful treatment and remained symptom-free. All congenital SGS (3/8) patients were successfully treated. Two patients failed EACSBD for reasons unrelated to the procedure. One patient (1/8) remained intubated for 41 days post-operatively and required a tracheostomy for respiratory failure secondary to severe pulmonary tuberculosis. Three children had post-operative aspiration, two resolved with speech therapy. One child went home on nasogastric feeding. No procedural complications were reported. Conclusion: This is the first study from sub-Saharan Africa to describe a series of EACSBD in selective paediatric SGS. All congenital cases in our cohort were successfully treated, contributing to an overall success rate of 75%. EACSBD is therefore a safe and effective surgical option for selected paediatric subglottic stenosis. It is well-suited for resource-limited settings by offering a definitive solution that may avert a tracheostomy. However, it should be used with caution in patients with additional laryngeal pathology, those with higher risk of aspiration, and in cases of co-existing lung disease. Careful patient selection is therefore essential to achieve optimal outcomes.